Soil fertility evaluation and crop development in Kubutambahan Sub-district, Buleleng District, Indonesia - MADE SRI SUMARNIASIH; PUTU PERDANA KUSUMA WIGUNA; PUTU OKI BIMANTARA; I NENGAH KARNATA (Asian Journal of Agriculture, 2026)
Abstract. Sumarniasih MS, Wiguna PPK, Bimantara PO, Karnata IN. 2026. Soil fertility evaluation and crop development in Kubutambahan Sub-district, Buleleng District, Indonesia. Asian J Agric 10 (1): g100172. https://doi.org/10.13057/asianjagric/g100172. The productivity of agricultural land is strongly influenced by soil fertility, yet detailed and spatially explicit assessments remain limited in many parts of Bali despite its diverse agroecosystems. This study assessed soil fertility in Kubutambahan Sub-district, Buleleng District, Bali, Indonesia, by delineating Homogeneous Land Units (HLUs) using GIS-based spatial analysis and conducting representative soil sampling. Seven HLUs were analyzed for key soil chemical properties, including organic C, total P₂O₅, total K₂O, Cation Exchange Capacity (CEC), Base Saturation (BS), and pH, and fertility status was determined following national evaluation guidelines using the principle of the most limiting factor. The results indicate that soil fertility across the district is predominantly low to moderate, with organic carbon levels (1.33-1.71%) consistently identified as the most critical limiting factor. Approximately 68.2% of the area (8,380 ha) was classified as low fertility, while the remaining 31.8% (3,908 ha) exhibited medium fertility. Low organic matter, low CEC, and, in some areas, very low BS were the primary causes of reduced fertility, despite generally adequate levels of phosphorus and potassium. Statistical analysis showed that organic carbon was significantly correlated with CEC (r = 0.49, p < 0.05) and base saturation (r = 0.65, p < 0.01), confirming its key role as a controlling factor of soil fertility. These findings highlight organic carbon as the primary limiting factor and emphasize the need for HLU-based, site-specific management strategies focused on organic matter restoration to enhance soil fertility and agricultural productivity in the study area. This study provides the first spatially explicit soil fertility assessment at the sub-district scale in Kubutambahan and highlights the need for HLU-based, site-specific management strategies emphasizing organic matter restoration to support sustainable agricultural productivity.